Call book of modern quadrilles ... - Strassburg, Herman A. (Detroit, Mich., American Music Co., 1889)
The author of this manual declares that "every person should be able to dance ... quadrilles without the aid of a 'caller.'" Unlike other contemporary call books, Strassburg provides the calls as well as a brief description of the figures. The work also includes three waltz quadrilles (one is set for three couples) that are credited to the well-known dancing master E. W. Masters of Boston.
Cover title.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Quadrille (Dance) -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals; Prompting Quadrilles